Radiographic Quality of Single versus Multiple-Visit Root Canal Treatment Performed by Dental Students: A Case Control Study - Al-Manei, Kholod K (Iranian Endodontic Journal, 2018)
Introduction: The aim of this study was to compare the quality of root canal treatment provided by undergraduate dental students in relation to the number of dental visits. Methods and Materials: Root canal treatments done by 77 dental students were observed. For each student, one tooth treated in a single visit was matched and compared with a tooth treated in multiple visits. The effect of preoperative conditions on the quality of root canal treatment and the number of visits were analyzed. The quality of root canal treatment was determined by the following criteria: obturation length, density, taper, and presence of procedural errors. The data were statistically analyzed using an exact conditional logistic regression test, and the level of significance was set at 0.05. Results: There was no statistically significant association between single- and multiple-visit root canal treatment in terms of obturation length (P=0.263), obturation density (P=0.625), and obturation taper (P=1.00). The incidence of procedural errors in teeth which required a single visit (7.8%) was less but not significantly different from those treated in multiple visits (16.9%). The presence of preoperative conditions was not significantly associated with multiple-visit treatment. Conclusion: Within the limitations of the study, multiple-visit treatment was not associated with a better quality of root canal treatment compared to single-visit treatment. Keywords: Case Control; Endodontic Treatment; Multiple Visits; Radiographic Evaluation; Single Visit